Acoustofluidic control of bubble size in microfluidic flow-focusing configuration. Issue 4 (16th December 2014) - Chong, Zhuang Zhi; Tor, Shu Beng; Loh, Ngiap Hiang; Wong, Teck Neng; Gañán-Calvo, Alfonso M.; Tan, Say Hwa; Nguyen, Nam-Trung
Abstract : We report a new technology using acoustofluidic to achieve controllable manipulation of the size of the bubbles formed. Abstract : This paper reports a method to control the bubble size generated in a microfluidic flow-focusing configuration. With an ultrasonic transducer, we induce acoustic streaming using a forward moving, oscillating gas–liquid interface. The induced streaming substantially affects the formation process of gas bubbles. The oscillating interface acts as a pump that increases the gas flow rate significantly and forms a larger bubble. This method is applicable to a wide range of gas pressure from 30 to 90 kPa and flow rate from 380 to 2700 μL h −1 . The bubble size can be tuned repeatedly with the response time on the order of seconds. We believe that this method will enhance the capability of a microfluidic bubble generator to produce a tunable bubble size.